2010
DOI: 10.1137/090747701
|View full text |Cite
|
Sign up to set email alerts
|

Superconvergence of Discontinuous Galerkin and Local Discontinuous Galerkin Schemes for Linear Hyperbolic and Convection-Diffusion Equations in One Space Dimension

Abstract: In this paper, we study the superconvergence property for the discontinuous Galerkin (DG) and the local discontinuous Galerkin (LDG) methods, for solving one-dimensional time dependent linear conservation laws and convection-diffusion equations. We prove superconvergence towards a particular projection of the exact solution when the upwind flux is used for conservation laws and when the alternating flux is used for convection-diffusion equations. The order of superconvergence for both cases is proved to be k +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
93
0
9

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(105 citation statements)
references
References 19 publications
(27 reference statements)
3
93
0
9
Order By: Relevance
“…It was shown that when discretizing the equations in a dual consistent [9,17] way, the order of accuracy of the output functional was higher than the FD solution itself. This superconvergent behaviour was seen already in [3] for FEM and in [7] for DG, but it had not been previously proven for finite difference schemes.…”
Section: Introductionmentioning
confidence: 63%
See 2 more Smart Citations
“…It was shown that when discretizing the equations in a dual consistent [9,17] way, the order of accuracy of the output functional was higher than the FD solution itself. This superconvergent behaviour was seen already in [3] for FEM and in [7] for DG, but it had not been previously proven for finite difference schemes.…”
Section: Introductionmentioning
confidence: 63%
“…In order to derive a stable and spatially dual consistent scheme, (45) has to be rewritten as a first order system in the same way as in the local discontinuous Galerkin (LDG) method [46]. It has been shown that the LDG method has interesting superconvergent features not only for functionals, but also for the solution itself [7,29,47]. We hence adapt the LDG formulation and rewrite (45) as…”
Section: The Heat Equationmentioning
confidence: 99%
See 1 more Smart Citation
“…Тогда в многомерном случае на неструктурированной сетке при сохранении качества сеточных элементов DG обладает аппроксимацион-ной ошибкой O(h p ) и позволяет найти решение с точностью O(h p+1/2 ) в норме L 2 [2]. В одномерном случае на неравномерной сетке порядок аппроксимации также равен p, но порядок точности равен p + 1 [3].…”
Section: Introductionunclassified
“…Among these is the local discontinuous Galerkin (LDG) method, which was proposed in [3] and [9] by separating higher order operators into systems of first order equations so that classical DG methods can be extended to problems with second order operators, especially for convection-diffusion and hyperbolic equations. The state of the art of the development of these methods and their applications can be found in [1,2,5,7,10].In this work, we apply the LDG method to 1-D singularly perturbed problems with Dirichlet boundary conditions: …”
mentioning
confidence: 99%